Epidemiology, Clinical characteristics, Laboratory Findings Of Bronchiolitis In Hospitalized Children - saleh, majeed; Shukr, mohammed (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Bronchiolitis is the most common disease of the lower respiratory tract during the first year of life. Which is usually caused by respiratory syncytial virus. The treatment is usually supportive, so epidemiology, clinical, laboratory, and radiologic findings might facilitate early diagnosis and treatment of bronchiolitis cases.Objectives: The aim of our study was to evaluate the clinical characteristics and laboratory findings of children hospitalized due to bronchiolitis.Patients and Methods: In this cross sectional study 143 patients with bronchiolitis were selected who age 1-24 months old who were admitted to the Fallujah teaching hospital for women and children, over the period of 6 months from 1st of October 2018 to 1st of April2019. The patients were selected from large number of cases admitted to Hospital according to bronchiolitis criteria.Results: A total number of 143 patients were included in this study, 52.4% were male and 47.6% were female. The most common clinical findings were tachypnea, dyspnea, cough, fever, wheeze consecutively. Hyperinflation was the most common radiological study, while lymphocytosis was the most common laboratory finding.Conclusions: In our study Bronchiolitis was mostly diagnosed in the first 6 months of age, most of patients from urban area, tachypnea was most common sign while hyperinflation was the most common radiological finding and lymphocytosis was most common CBC finding. These data might facilitate early diagnoses and treatment of bronchiolitis cases.